2011
DOI: 10.1038/jhh.2011.85
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different adiposity measures on the relation between serum uric acid and blood pressure in young adults

Abstract: Serum uric acid (SUA) concentration is independently associated with blood pressure (BP) in adults. We examined this association in young adults at an age where anti-hypertension treatment, other potential confounding factors and co-morbidity are unlikely to occur. We assessed BP, anthropometric variables including weight, height, waist circumference (WC), body fat percent (using bioimpedance), lifestyle behaviors, SUA and blood lipids in 549 participants aged 19-20 years from a population-based cohort study (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…3 It is critical for the reader to be cognizant of this premise and, moreover, recognize that our analysis looked at the environmentally unconfounded and unidirectional association between GLUT9 genotype and blood pressure, as opposed to the easily confoundable association between SUA and blood pressure. 2 Indeed, as proof of concept, we showed in Table 2 of our original article that SUA was strongly associated with glucose, renal function, and body mass index (P values of 2.5 Â 10 À8 , 1.4 Â 10 À14 , and 1.5 Â 10 À31 , respectively), while, as expected, the GLUT9 genotype was not associated with these factors. 2 Conferring with the premise of MR and the complete lack of association between GLUT9 genotype and glucose, obesity, dyslipidemia, and renal function, we suitably did not adjust for them in our analysis.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…3 It is critical for the reader to be cognizant of this premise and, moreover, recognize that our analysis looked at the environmentally unconfounded and unidirectional association between GLUT9 genotype and blood pressure, as opposed to the easily confoundable association between SUA and blood pressure. 2 Indeed, as proof of concept, we showed in Table 2 of our original article that SUA was strongly associated with glucose, renal function, and body mass index (P values of 2.5 Â 10 À8 , 1.4 Â 10 À14 , and 1.5 Â 10 À31 , respectively), while, as expected, the GLUT9 genotype was not associated with these factors. 2 Conferring with the premise of MR and the complete lack of association between GLUT9 genotype and glucose, obesity, dyslipidemia, and renal function, we suitably did not adjust for them in our analysis.…”
mentioning
confidence: 54%
“…Indeed, this was the reason for our performing the Mendelian randomization (MR) analysis. 2 MR is based on the tenet that genotype, which is randomly assigned during gamete formation and fixed, cannot be modified by any of the traditional risk factors (e.g., obesity and diabetes) that occur after conception and hence is not confounded by them. 3 It is critical for the reader to be cognizant of this premise and, moreover, recognize that our analysis looked at the environmentally unconfounded and unidirectional association between GLUT9 genotype and blood pressure, as opposed to the easily confoundable association between SUA and blood pressure.…”
mentioning
confidence: 99%
“…In general, this finding is consistent with most previous studies [41,49] that suggested the high SUA and TG level were risk factors for hypertension. Although previous studies [45,50,51] have explored the association and/or interaction analysis between BMI and SUA levels and BP, no consistent results are pointing to such associations. Lee et al [45], using data from 45,098 Koreans who underwent health examinations at Korea Association of Health Promotion with no history of taking drugs related with UA and/or BP, found that SUA levels were positively associated with SBP and DBP in men aged < 40 years after adjustment for age, diabetes, dyslipidemia, BMI, and eGFR; However, no significant associations were found in men aged 60 years or older.…”
Section: Discussionmentioning
confidence: 98%
“…Lee et al [45], using data from 45,098 Koreans who underwent health examinations at Korea Association of Health Promotion with no history of taking drugs related with UA and/or BP, found that SUA levels were positively associated with SBP and DBP in men aged < 40 years after adjustment for age, diabetes, dyslipidemia, BMI, and eGFR; However, no significant associations were found in men aged 60 years or older. Lyngdoh et al [50], assessing 549 individuals aged 19-20 years, found that SUA levels tended to be positively associated with DBP and SBP in men. Moreover, the strength of the SUA-BP association was similar in women.…”
Section: Discussionmentioning
confidence: 99%
“…We found a significant association between BMI and glucose only in females even though males had higher blood glucose levels than females. A possible explanation for the observed sex differences could be the greater adiposity, in particular fat mass, in females than in males [41]. The influence of abdominal fat, which is particularly active metabolically [42], may not be fully captured by the measurement of BMI [43] and might be a key determinant of some of the observed sex differences.…”
Section: Discussionmentioning
confidence: 99%